Protective immunity against influenza in HLA-A2 transgenic mice by modified vaccinia virus Ankara vectored vaccines containing internal influenza proteins. (17th February 2017) - Di Mario, Giuseppina; Sciaraffia, Ester; Facchini, Marzia; Gubinelli, Francesco; Soprana, Elisa; Panigada, Maddalena; Bernasconi, Valentina; Garulli, Bruno; Siccardi, Antonio; Donatelli, Isabella; Castrucci, Maria R.
Abstract: Background: The emergence of novel strains of influenza A viruses with hemagglutinins (HAs) that are antigenically distinct from those circulating in humans, and thus have pandemic potential, pose concerns and call for the development of more broadly protective influenza vaccines. In the present study, modified vaccinia virus Ankara (MVA) encoding internal influenza antigens were evaluated for their immunogenicity and ability to protect HLA-A2.1 transgenic (AAD) mice from infection with influenza viruses. Methods: MVAs expressing NP (MVA-NP), M1 (MVA-M1) or polymerase PB1 (MVA-PB1) of A/California/4/09 (CA/09) virus were generated and used to immunize AAD mice. Antibodies and CD8+T cell responses were assessed by ELISA and ELISPOT, respectively, and challenge experiments were performed by infecting vaccinated mice with CA/09 virus. Results : CD8+T cells specific to immunodominant and subdominant epitopes on the internal influenza proteins were elicited by MVA-based vectors in AAD mice, whereas influenza-specific antibodies were detected only in MVA-NP-immunized mice. Both M1- and NP-based MVA vaccines, regardless of whether they were applied individually or in combination, conferred protection against lethal influenza virus challenge. Conclusion: Our data further emphasize the promising potential of MVA vector expressing internal antigens toward the development of a universal influenza vaccine.